Remote Sensing Data Analysis for Urban Planning and Land Use Change - Xu, Jingyang; Zheng, Yutong (Transactions on Environment, Energy and Earth Sciences, 2024)
With the acceleration of urbanization, rational use of land resources and effective town planning and layout have become particularly important. Through its advantages of high temporal and spatial resolution, remote sensing technology provides strong data support for dynamic monitoring, precise planning and management of land use. This study thoroughly analyzed urban planning and land use changes over the past decades using remote sensing technology, revealing the advantages of remote sensing application in land resource management. The study shows that remote sensing technology can provide continuous and multi-period land use images, effectively monitor land use changes, and provide scientific basis for land use planning and dynamic adjustment. In addition, remote sensing data's high resolution and automated processing capability significantly improves the accuracy of land use type classification, providing strong support for urban planning and land management decision-making. Integrating remote sensing data with GIS, deep learning and other technologies, this paper hopes further to promote the intelligence and refinement of land use planning, and make significant contributions to achieving the goal of sustainable development.